Quality of surgical management of placenta accreta spectrum in a tertiary center in Sri Lanka: baseline study for quality improvement project: problems and solutions - Vindya Wijesinghe; Mohamed Rishard; Sriskanthan Srisanjeevan (BMC, 2022)
Abstract Introduction Placenta accreta spectrum (PAS) is associated with a multitude of maternal and fetal complications. Events related to its management have resulted in significant psychological morbidity, with lifelong consequences which warrant continuous support to cope with their lives. The objective of the study is to highlight the importance of multidisciplinary holistic care and explore room for improvement in the provision of care for women with PAS. Methods Our study was conducted on deliveries complicated with PAS from January 2019 to June 2021. 27 women were diagnosed with PAS during this period and received treatment. Impact of life event scale- revised (IES-R) and short form health survey-36(SF-36) questionnaires were administered to assess the impact of PAS on their lives. In depth interviews were conducted with the women. A multidisciplinary team meeting was later conducted to formulate a comprehensive care plan for women with PAS. Results The response rate was 96.2%. Mean age of the sample is 34.1 years (SD 4.3). Interval to current pregnancy varies from 0.6 years to 10 years with mean of 4.6 years. Mean gestational age of diagnosis of PAS was 25.4(SD 6.7) weeks. The care bundle provided for women with PAS was evaluated in all cases. Surgery was conducted electively in 82% of patients. Blood transfusions were noted in 85%. Mean pre-operative stay was 9.5 days (SD 8.3) and mean post-operative stay was 8.8 days (SD 8). Total hospital stay ranged from 6 to 48 days (mean 19.5 days, SD 11.4). IES-R scores were significant in 4/26 patients. There was no correlation with the interval from the surgery with any of the subscales or with the total scores. The lapsed time after the surgery had a significant correlation with physical functioning and pain domains of the SF-36 questionnaire. Description of the experience, loss of femininity with loss of the uterus, concerns and fears about the future and measures to improve the quality of care were the themes identified and described. A multidisciplinary team meeting, consisting of consultant obstetricians performing surgery for PAS, anesthetists, hematologist, transfusion medicine specialist, urologist, physiotherapist, nutritionist and nursing officers from ICU and wards, was held and their contributions helped to map out a definitive care plan. Conclusions PAS is associated with long term physical and psychological morbidity. Continuous support through quarterly clinic visits and telephone conversations may alleviate the psychological trauma. However, some physical disabilities may be lifelong and life changing. Importance of reducing primary caesarean section and promoting trial of labour after caesarean delivery should be promoted among patients and caregivers.